Проблеми іншомовної професійно орієнтованої підготовки майбутніх фахівців-аграріїв - Піддубцева, Ольга Ігорівна; Piddubtseva, Olga (Запорізький національний університет, 2018)
У статті визначено місце іншомовної професійно орієнтованої підготовки майбутніх фахівців-аграріїв в системі вищої освіти. Охарактеризовані основні поняття “професійна підготовка майбутнього фахівця-аграрія”, “професія”, “підготовка”, “агроном”. Проаналізовано основні документи, що регламентують процес викладання дисципліни “Іноземна мова (за професійним спрямуванням)”. The problem of foreign language professionally oriented education is the subject of wide speculation of basic research as well as many doctoral and Ph.D. thesis in the strategy of the professional education for specialist in different professions. Our research considers the concepts “professional education of the future specialist-agrarian”, “profession”, “education”, “agronomist”. The future agronomist is the specialist that takes up a post of the agronomist on graduating from university, that has the fixed amount of functional liabilities according to normative documents of enterprise. The professional education of the future agronomist in the university is considered as the process of the formation the figure of the future specialist that is able to solve the delivered assignments using the knowledge, abilities and skills, and also to be ready for the foreign language professionally oriented communication. The curriculum of the professional education of the future agronomist in the university provides for the learning not only obligatory professional subjects, but also the humanitarians subjects among which is the subject “Foreign language for specific purposes”. The aim of the teaching the subject “Foreign language for specific purposes” in the university is to master the necessary lexical and grammatical material for the practical using the getting knowledge in the future professional activity. The peculiarity of the foreign language professionally oriented in agrarian university is the small quantity of the contact hours for the teaching the subject “Foreign language for specific purposes”.
The problems of the foreign language professionally oriented education of future specialists-agrarians
Keywords: професійна підготовка; professional education; агроном; agronomist; аграрний заклад вищої освіти; agrarian institution of higher education; іноземна мова (за професійним спрямуванням); foreign language for specific purposes